Fast and Reliable PCR Amplification from Aspergillus fumigatus Spore Suspension Without Traditional DNA Extraction. Issue 1 (20th August 2019) - Fraczek, Marcin G.; Zhao, Can; Dineen, Lauren; Lebedinec, Ressa; Bowyer, Paul; Bromley, Michael; Delneri, Daniela
Abstract: Aspergillus fumigatus is an opportunistic human pathogenic mold. DNA extraction from this fungus is usually performed by mechanical perturbation of cells, as it possesses a rigid and complex cell wall. While this is not problematic for single isolates, it can be time consuming for large numbers of strains if using traditional DNA extraction procedures. Therefore, in this article we describe a fast and efficient thermal‐shock method to release DNA from spores of A. fumigatus and other filamentous fungi without the need for complex extraction methods. This is especially important for high‐throughput PCR analyses of mutants in 96‐ or 384‐well formats in a very short period of time without any concern about sample cross‐contamination. This method is currently being used to validate the protein‐coding gene and non‐coding RNA knockout libraries in A. fumigatus generated in our laboratory, and could be used in the future for diagnostics purposes. © 2019 The Authors.